Reflections on Confucianism in Four Women Characters in The Sword and The Brocade - Anfrida Cathlyn (Institute of Research and Community Outreach - Petra Christian University, 2022)
Chinese dramas, in recent years, have gained popularity in the international market. To be precise, historical dramas have a market that has increased year by year since 2017. This thesis is about Confucian virtues found in four women characters in a historical Chinese drama titled The Sword and The Brocade. This television drama intrigues the writer to analyze four women characters Luo Shi Yi Niang, Qiao Lian Fang, Madam Xu, and Xiang Yi Zhen in the story because The Sword and The Brocade shows the dynamic relationship between the women characters and the plot is wrapped in historical settings but with modern perspective. This thesis aims to find out how the female characters’ actions reflect Confucian virtues and what the impacts of the reflected actions are for them. The analysis is based on Confucianism; focusing on five Confucian virtues: loyalty, filial piety, wisdom, benevolence, and harmony. Moreover, the analysis begins with the women’s way to express the Confucian virtues within their actions and then moves to how the actions from reflecting the virtues impacted their life. From expressing loyalty to harmony, Luo Shi Yi Niang, Qiao Lian Fang, Madam Xu, and Xiang Yi Zhen get positive changes in their lives like getting a new status, achieving their goals, making their family proud, and getting positive aftermath from their past actions. The finding is these women prove that women can gain benefits from Confucianism that is known to be patriarchal and these women are the example of how ancient belief can be modernized to suit nowadays’ modern issues and the story is suitable for everyone and in every era.